Composition and authentication of commercial and home-made white truffle-flavored oils. (May 2018) - Wernig, Florian; Buegger, Franz; Pritsch, Karin; Splivallo, Richard
Abstract: Truffle-flavored olive oils sell at a high premium compared to unflavored oils, yet, their rarely contain either real truffles or natural truffle aroma. Our aim here was to characterize truffle oils and explore techniques for authentication. Specifically, we characterized and compared by metabolic profiling and stable isotope ratio analysis the flavors emitted by commercial and home-made truffle-flavored oils (prepared with natural and synthetic flavors), non-flavored oils, and actual fruiting bodies of the white truffle Tuber magnatum . Stable isotope ratio analysis (δ 13 C) of 2, 4-dithiapentane, a characteristic truffle odorant detected in most flavored oil samples, could not differentiate between natural and synthetic flavors. By contrast, metabolic profiling revealed that truffle flavor was imprinted to oils by four to six sulfur containing volatiles, two of which (dimethyl sulfoxide and dimethyl sulfone) were exclusively detected in commercial oils, regardless of their synthetic or natural labeling. Overall our results also highlight inconsistencies in product labelling and question the authenticity of oils claiming to contain only natural truffle flavors. Highlights: The composition of white truffle flavor used in commercial olive oils is revealed. White truffle flavor is impaired to oils by 4–6 sulfur containing volatiles. Dimethyl sulfoxide and dimethyl sulfone are markers of commercial oils.